Faktor yang Berhubungan dengan Praktek Pemberian ASI Eksklusif di Wilayah Kerja Puskesmas Rada Mata Kabupaten Sumba Barat Daya - Jeniati Bulu; Lewi Jutomo; Daniela L. A. Boeky (Media Kesehatan Masyarakat, 2021)
Exclusive breastfeeding is the provision of breast milk without other additional food. This study aims to determine the factors associated with the practice of exclusive breastfeeding in infants aged 0 - 6 months at the Rada Mata Public Health Center, Southwest Sumba Regency, which was conducted from August to October 2020. This type of research was an analytical observational with cross-sectional study. Sampling in this study were 75 respondents who had children aged 6-12 months. Data processing was carried out descriptively and analytically. The results showed a significant relationship between education, knowledge, employment, support from health workers, family support for exclusive breastfeeding for infants 0-6 months at the Rada Mata Puskesmas, Southwest Sumba Regency. Mothers who have a good education have the opportunity to provide exclusive breastfeeding for their babies, as well as work, support from health workers and family support for mothers under five. Therefore, it is necessary to collaborate between health workers and the local community, especially mothers who have babies aged 0 - 6 months so that the program can be implemented properly.